Manufacturing method for all-solid-state batteries
By employing symmetric electrode structures and soft cross-linked polymer electrolytes, the method enhances volume energy density and prevents warping in the manufacturing of all-solid-state batteries.
Patent Information
- Application Number
- JP2021109937
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-07-01
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-07-01
AI Technical Summary
Existing methods for manufacturing all-solid-state batteries face challenges in reducing the number of steps to suppress warping and improving volume energy density, particularly due to the continuous stacking of current collectors.
The method involves preparing positive and negative electrode structures with high structural symmetry and using soft cross-linked polymer electrolytes in the solid electrolyte layers to prevent warping during pressing. This approach eliminates the continuous stacking of current collectors, enhancing volume energy density.
The method effectively increases volume energy density while suppressing warping in the manufacturing process of all-solid-state batteries.
Smart Images

Figure 0007669830000002 
Figure 0007669830000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for manufacturing an all-solid-state battery. [Background technology]
[0002] An all-solid-state battery is a battery that has a solid electrolyte layer between a positive electrode layer and a negative electrode layer, and has the advantage that it is easier to simplify safety devices compared to liquid batteries that have an electrolyte solution containing a flammable organic solvent.
[0003] For example, Patent Document 1 discloses a method for producing an all-solid-state battery including the following steps (A) to (F). (A) forming a first electrode layer by disposing a first electrode active material layer containing a first electrode active material on each of both surfaces of a first current collector having a first main surface and a second main surface; (B) disposing a solid electrolyte layer containing a solid electrolyte on each of the first electrode active material layers disposed on both sides; (C) disposing a second electrode active material layer containing a second electrode active material and a second current collector on the solid electrolyte layer disposed on each of the first electrode active material layers, such that the second electrode active material layer is in contact with the solid electrolyte layer; (D) a step of pressing a laminate including the second current collector, the second electrode active material layer, the solid electrolyte layer, the first electrode active material layer, the first current collector, the first electrode active material layer, the solid electrolyte layer, the second electrode active material layer, and the second current collector produced in the steps (A) to (C) to produce a battery unit; (E) repeating the steps (A) to (D) to fabricate a plurality of the battery units; (F) stacking the plurality of battery units
[0004] The object of Patent Document 1 is to reduce the number of steps for suppressing warpage compared to conventional methods. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2015-125872 A Summary of the Invention [Problem to be solved by the invention]
[0006] In Patent Document 1, in step (F), a plurality of battery units are stacked. A second current collector is disposed on the outermost surface of each battery unit. Therefore, at the boundary between adjacent battery units, the second current collector of one battery unit and the second current collector of the other battery unit are continuously stacked. Since these second current collectors have a common function, there is room for improvement from the viewpoint of increasing the volumetric energy density.
[0007] The present disclosure has been made in consideration of the above-described circumstances, and has a main object to provide a manufacturing method for an all-solid-state battery capable of improving the volumetric energy density while suppressing the occurrence of warping. [Means for solving the problem]
[0008] The present disclosure provides a method for producing an all-solid-state battery, the method comprising: a positive electrode structure preparing step of preparing a positive electrode structure having a positive electrode current collector and positive electrode layers arranged on both sides of the positive electrode current collector; a negative electrode structure preparing step of preparing a negative electrode structure having a negative electrode current collector and negative electrode layers arranged on both sides of the negative electrode current collector; an electrode laminate forming step of bonding the positive electrode structure and the negative electrode structure by disposing a first solid electrolyte layer containing a first polymer electrolyte between the positive electrode structure and the negative electrode structure to form an electrode laminate; and a battery laminate forming step of bonding the pair of electrode laminates by disposing a second solid electrolyte layer containing a second polymer electrolyte between the positive electrode layer of one of the electrode laminates and the negative electrode layer of the other electrode laminate to form a battery laminate, wherein the first polymer electrolyte and the second polymer electrolyte are each a crosslinked polymer electrolyte in which a polymer component is crosslinked.
[0009] According to the present disclosure, the occurrence of warping due to pressing can be suppressed by using a positive electrode structure and a negative electrode structure with high structural symmetry and by using a soft first solid electrolyte layer and a soft second solid electrolyte layer. Furthermore, according to the present disclosure, by going through the above-mentioned steps, an all-solid-state battery is produced without continuously stacking the positive electrode current collector or the negative electrode current collector. Therefore, the volumetric energy density can be improved. Effect of the Invention
[0010] The manufacturing method of an all-solid-state battery according to the present disclosure has an effect of improving the volumetric energy density while suppressing the occurrence of warping. [Brief description of the drawings]
[0011] [Figure 1] 1A to 1C are schematic cross-sectional views illustrating a method for producing an all-solid-state battery according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The manufacturing method of the all-solid-state battery in the present disclosure will be described in detail below with reference to the drawings. Each of the drawings shown below is a schematic illustration, and the size and shape of each part are appropriately exaggerated to facilitate understanding. In addition, hatching showing the cross section of a member is appropriately omitted in each drawing.
[0013] FIG. 1 is a schematic cross-sectional view illustrating a method for manufacturing an all-solid-state battery according to the present disclosure. In the method for manufacturing an all-solid-state battery shown in FIG. 1, first, as shown in FIG. 1(a), a positive electrode structure 11 having a positive electrode current collector 4 and a positive electrode layer 1 arranged on both sides of the positive electrode current collector 4 is prepared (positive electrode structure preparation step). Next, as shown in FIG. 1(b), a negative electrode structure 12 having a negative electrode current collector 5 and a negative electrode layer 2 arranged on both sides of the negative electrode current collector 5 is prepared (negative electrode structure preparation step). The positive electrode structure 11 and the negative electrode structure 12 may be prepared by self-manufacturing or may be purchased from another party.
[0014] Next, as shown in FIG. 1(c), a first solid electrolyte layer 3a containing a first polymer electrolyte is disposed between the positive electrode structure 11 and the negative electrode structure 12, and the positive electrode structure 11 and the negative electrode structure 12 are bonded together to form an electrode laminate 13 (electrode laminate forming step). Next, as shown in FIG. 1(d), in a pair of electrode laminates (13x, 13y), a second solid electrolyte layer 3b containing a second polymer electrolyte is disposed between the positive electrode layer 1 in one electrode laminate 13y and the negative electrode layer 2 in the other electrode laminate 13x, and the pair of electrode laminates (13x, 13y) are bonded together to form a battery laminate 14 (battery laminate forming step). The first polymer electrolyte in the first solid electrolyte layer 3a and the second polymer electrolyte in the second solid electrolyte layer 3b are crosslinked polymer electrolytes in which the polymer components are crosslinked. This results in a parallel-connected all-solid-state battery.
[0015] According to the present disclosure, the occurrence of warping due to pressing can be suppressed by using a positive electrode structure and a negative electrode structure with high structural symmetry and by using a soft first solid electrolyte layer and a soft second solid electrolyte layer. Specifically, the positive electrode structure has a positive electrode layer disposed on both sides of a positive electrode current collector, and has high structural symmetry. Therefore, the occurrence of warping in the positive electrode structure can be suppressed by pressing during the preparation of the positive electrode structure. In particular, when the positive electrode layer contains an inorganic solid electrolyte, it is necessary to press with a very high pressure, but even if such pressing is performed, the occurrence of warping in the positive electrode structure can be suppressed. The same applies to the negative electrode structure. Furthermore, since the first solid electrolyte layer contains a first polymer electrolyte that is softer than the inorganic solid electrolyte, it is not necessary to press with a high pressure when bonding the positive electrode structure and the negative electrode structure together. Therefore, it is possible to suppress the occurrence of warping during the preparation of the electrode stack. Similarly, since the second solid electrolyte layer contains a second polymer electrolyte that is softer than the inorganic solid electrolyte, it is not necessary to press with a high pressure when bonding a pair of electrode stacks together. Therefore, it is possible to suppress the occurrence of warping during the preparation of the battery stack.
[0016] Furthermore, according to the present disclosure, by going through the above-mentioned steps, an all-solid-state battery is produced without continuously stacking the positive electrode current collector or the negative electrode current collector, thereby improving the volumetric energy density.
[0017] 1. Positive electrode structure preparation process The positive electrode structure preparation step in the present disclosure is a step of preparing a positive electrode structure having a positive electrode current collector and positive electrode layers disposed on both sides of the positive electrode current collector. For example, a method of forming the positive electrode structure includes a method of applying a slurry containing a constituent material of the positive electrode layer and a dispersion medium onto the positive electrode current collector and then drying the slurry.
[0018] Examples of the material of the positive electrode current collector include SUS, aluminum, nickel, and carbon. The positive electrode layer contains at least a positive electrode active material. Examples of the positive electrode active material include an oxide active material. Examples of the oxide active material include LiCoO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc., rock salt layered active materials, LiMn2O4, Li4Ti5O 12 and olivine type active materials such as LiFePO4. A protective layer containing a Li-ion conductive oxide may be formed on the surface of the oxide active material. The shape of the positive electrode active material may be, for example, particulate.
[0019] The positive electrode layer preferably contains a solid electrolyte. Examples of the solid electrolyte include inorganic solid electrolytes and polymer electrolytes. Among them, inorganic solid electrolytes are preferable because they have high ionic conductivity.
[0020] Examples of inorganic solid electrolytes include sulfide solid electrolytes, oxide solid electrolytes, and halide solid electrolytes. In addition, the inorganic solid electrolyte may be glass (amorphous body), glass ceramics, or crystals. Glass can be obtained, for example, by amorphizing raw materials. Glass ceramics can be obtained, for example, by subjecting glass to heat treatment. Crystals can be obtained, for example, by heating raw materials.
[0021] The sulfide solid electrolyte preferably contains, for example, Li, A (A is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S. The sulfide solid electrolyte may further contain at least one of O (oxygen) and a halogen. Examples of the halogen include F, Cl, Br, and I. The sulfide solid electrolyte may contain only one type of halogen, or may contain two or more types of halogen. In addition, when the sulfide solid electrolyte contains an anion element other than S (for example, O and a halogen), it is preferable that the molar ratio of S is the largest among all the anion elements.
[0022] The sulfide solid electrolyte has an anion structure with an ortho composition (PS4 3- Structure: SiS4 4- Structure, GeS4 4- Structure: AlS3 3- Structure, BS4 3- It is preferable that the anion structure has an ortho-composition as a main component of the anion structure, because the anion structure has high chemical stability. The ratio of the anion structure having the ortho-composition to all the anion structures in the sulfide solid electrolyte is, for example, 50 mol % or more, or may be 60 mol % or more, or may be 70 mol % or more.
[0023] The sulfide solid electrolyte may have a crystal phase having ion conductivity, such as a Thio-LISICON type crystal phase, a LGPS type crystal phase, or an Argyrodite type crystal phase.
[0024] The inorganic solid electrolyte may be in the form of particles, for example.
[0025] The proportion of the solid electrolyte in the positive electrode layer is, for example, 10% by volume or more, and may be 20% by volume or more, while the proportion of the solid electrolyte in the positive electrode layer is, for example, 60% by volume or less, and may be 50% by volume or less.
[0026] The positive electrode layer may contain a conductive material. Examples of the conductive material include carbon materials. The positive electrode layer may also contain a binder. Examples of the binder include fluoride-based binders. The thickness of the positive electrode layer is, for example, 0.1 μm or more and 1000 μm or less.
[0027] The positive electrode structure may have a bonding solid electrolyte layer containing an inorganic solid electrolyte on the surface of the positive electrode layer (the surface opposite to the positive electrode current collector). The bonding solid electrolyte layer preferably contains a sulfide solid electrolyte as the inorganic solid electrolyte. The bonding solid electrolyte layer preferably has the same area as the positive electrode layer when the all-solid-state battery is viewed in a plan view along the thickness direction. As a method for forming the bonding solid electrolyte layer, for example, a method of laminating the positive electrode layer in the positive electrode structure and the bonding solid electrolyte layer formed on the transfer base material, pressing, and then peeling off the transfer base material can be mentioned. As a method for forming the bonding solid electrolyte layer, for example, a method of applying a slurry containing a constituent material of the bonding solid electrolyte layer and a dispersion medium onto the transfer base material, and then drying can be mentioned.
[0028] 2. Negative electrode structure preparation process The negative electrode structure preparation step in the present disclosure is a step of preparing a negative electrode structure having a negative electrode current collector and a negative electrode layer disposed on both sides of the negative electrode current collector. For example, a method of forming the negative electrode structure includes a method of applying a slurry containing a constituent material of the negative electrode layer and a dispersion medium onto the negative electrode current collector and then drying the slurry.
[0029] Examples of the material of the negative electrode current collector include SUS, copper, nickel, and carbon. The negative electrode layer contains at least a negative electrode active material. Examples of the negative electrode active material include metal active materials such as Si, Sn, and Li; carbon active materials such as graphite; and oxide active materials such as lithium titanate. The negative electrode active material may be a Si-based active material that contains at least Si. Examples of the Si-based active material include simple Si, Si alloys, and Si oxides. The Si alloy preferably contains Si element as a main component. In the Si alloy, the ratio of Si is, for example, 50 at% or more, may be 70 at% or more, or may be 90 at% or more.
[0030] The negative electrode layer preferably contains a solid electrolyte. Examples of the solid electrolyte include inorganic solid electrolytes and polymer electrolytes. Among them, inorganic solid electrolytes are preferable because they have high ionic conductivity. The inorganic solid electrolyte is the same as that described in the above "1. Positive electrode structure preparation step".
[0031] The proportion of the solid electrolyte in the negative electrode layer is, for example, 10% by volume or more, and may be 20% by volume or more, while the proportion of the solid electrolyte in the negative electrode layer is, for example, 60% by volume or less, and may be 50% by volume or less.
[0032] The negative electrode layer may contain a conductive material. The negative electrode layer may also contain a binder. The conductive material and the binder are the same as those described in "1. Positive electrode structure preparation step" above. The thickness of the negative electrode layer is, for example, 0.1 μm or more and 1000 μm or less.
[0033] The negative electrode structure may have a bonding solid electrolyte layer containing an inorganic solid electrolyte on the surface of the negative electrode layer (the surface opposite to the negative electrode current collector). The bonding solid electrolyte layer preferably contains a sulfide solid electrolyte as the inorganic solid electrolyte. The bonding solid electrolyte layer preferably has the same area as the negative electrode layer when the all-solid-state battery is viewed in a plan view along the thickness direction. The method for forming the bonding solid electrolyte layer is as described above.
[0034] 3. Electrode laminate formation process The electrode laminate formation process in the present disclosure is a process of bonding the positive electrode structure and the negative electrode structure by disposing a first solid electrolyte layer containing a first polymer electrolyte between the positive electrode structure and the negative electrode structure, thereby forming an electrode laminate.
[0035] The first solid electrolyte layer contains a first polymer electrolyte. The first polymer electrolyte is a crosslinked polymer electrolyte in which a polymer component is crosslinked. Examples of the polymer component include polyether-based polymers, polyester-based polymers, polyamine-based polymers, and polysulfide-based polymers, and among these, polyether-based polymers are preferred. This is because they have high ionic conductivity and excellent mechanical properties such as Young's modulus and breaking strength.
[0036] The polyether polymer has a polyether structure in the repeating unit. The polyether polymer preferably has a polyether structure in the main chain of the repeating unit. Examples of the polyether structure include a polyethylene oxide (PEO) structure and a polypropylene oxide (PPO) structure. The polyether polymer preferably has a PEO structure as a main repeating unit. In the polyether polymer, the proportion of the PEO structure in all repeating units is, for example, 50 mol % or more, may be 70 mol % or more, or may be 90 mol % or more. The polyether polymer may be, for example, a homopolymer or copolymer of an epoxy compound (e.g., ethylene oxide, propylene oxide).
[0037] The polymer component may have the following ion-conducting units: Examples of the ion-conducting units include polyethylene oxide, polypropylene oxide, polymethacrylic acid ester, polyacrylic acid ester, polydimethylsiloxane, polyacrylic acid, polymethacrylic acid, polyethylene vinyl acetate, polyimide, polyamine, polyamide, polyalkyl carbonate, polynitrile, polyphosphazene, polyolefin, and polydiene.
[0038] The weight average molecular weight (Mw) of the polymer component is not particularly limited, but is, for example, 1,000,000 or more and 10,000,000 or less. Mw is determined by gel permeation chromatography (GPC). The glass transition temperature (Tg) of the polymer component is, for example, 60° C. or less, and may be 40° C. or less, or 25° C. or less. The first polymer electrolyte may contain only one type of polymer component, or may contain two or more types.
[0039] Examples of polymerization initiators for crosslinking polymer components include peroxides such as benzoyl peroxide, di-tert-butyl peroxide, tert-butyl benzoyl peroxide, tert-butyl peroxyoctoate, and cumene hydroxyperoxide; and azo compounds such as azobisisobutyronitrile.
[0040] The first polymer electrolyte is preferably a dry polymer electrolyte. The dry polymer electrolyte refers to an electrolyte having a solvent component content of 5% by weight or less. The solvent component content may be 3% by weight or less, or may be 1% by weight or less. In particular, it is preferable that the solid electrolyte layer contains a dry polymer electrolyte, and the positive electrode layer and the negative electrode layer contain a sulfide solid electrolyte. This is because deterioration of the sulfide solid electrolyte caused by the solvent can be suppressed.
[0041] The dry polymer electrolyte may contain a supporting salt. Examples of the supporting salt include inorganic lithium salts such as LiPF6, LiBF4, LiClO4, and LiAsF6, and organic lithium salts such as LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(FSO2)2, and LiC(CF3SO2)3. The ratio of the supporting salt to the dry polymer electrolyte is not particularly limited. For example, when the dry polymer electrolyte has an EO unit (C2H5O unit), the EO unit is, for example, 5 molar parts or more, 10 molar parts or more, or 15 molar parts or more relative to 1 molar part of the supporting salt. On the other hand, the EO unit is, for example, 40 molar parts or less, and may be 30 molar parts or less relative to 1 molar part of the supporting salt.
[0042] The ratio of the first polymer electrolyte in the first solid electrolyte layer is, for example, 80% by volume or more, or may be 90% by volume or more, or may be 95% by volume or more, and the first solid electrolyte layer may contain only the first polymer electrolyte.
[0043] The first solid electrolyte layer is preferably self-supporting. "Self-supporting" refers to a layer that can maintain its shape even without the presence of other supports. For example, if a target solid electrolyte layer is placed on a substrate and the solid electrolyte layer maintains its shape when peeled off from the substrate, it can be said to be "self-supporting."
[0044] In addition, when the all-solid-state battery is viewed in a plan view along the thickness direction, the area of the first solid electrolyte layer may be larger than the area of the positive electrode layer. Similarly, the area of the first solid electrolyte layer may be larger than the area of the negative electrode layer. Here, the area of the positive electrode layer is S1, the area of the negative electrode layer is S2, and the area of the first solid electrolyte layer is S3. 31 Let S1 be the S 31 The ratio (S 31 / S1) is, for example, 1.01 or more, may be 1.03 or more, may be 1.05 or more, may be 1.1 or more, or may be 1.2 or more. 31 The ratio (S 31 / S1) is not particularly limited in upper limit, but S 31 If / S1 is large, the volumetric energy density may decrease. 31 The ratio (S 31 / S2) is, for example, 1.01 or more, may be 1.03 or more, may be 1.05 or more, may be 1.1 or more, or may be 1.2 or more. 31 The ratio (S 31 / S2) is not particularly limited, but S 31 If / S2 is large, the volumetric energy density may decrease.
[0045] 4. Battery stack formation process The battery stack formation process in the present disclosure is a process of bonding a pair of electrode stacks together to form a battery stack by disposing a second solid electrolyte layer containing a second polymer electrolyte between the positive electrode layer of one of the electrode stacks and the negative electrode layer of the other electrode stack.
[0046] The second solid electrolyte layer contains a second polymer electrolyte. The second polymer electrolyte is a crosslinked polymer electrolyte in which a polymer component is crosslinked. Details of the second polymer electrolyte and the second solid electrolyte layer are the same as those of the first polymer electrolyte and the first solid electrolyte layer described in "3. Electrode laminate forming process" above. The second polymer electrolyte in the second solid electrolyte layer and the first polymer electrolyte in the first solid electrolyte layer may have the same composition or may have different compositions.
[0047] In addition, when the all-solid-state battery is viewed in a plan view along the thickness direction, the area of the second solid electrolyte layer may be larger than the area of the positive electrode layer. Similarly, the area of the second solid electrolyte layer may be larger than the area of the negative electrode layer. Here, the area of the positive electrode layer is S1, the area of the negative electrode layer is S2, and the area of the second solid electrolyte layer is S3. 32 Let S1 be the S 32 The ratio (S 32 / S1), and S for S2 32 The ratio (S 32 / S2) are the same as above 31 / S1 and S 31 Same as / S2.
[0048] Also, in the present disclosure, three or more electrode laminates may be prepared, and the second solid electrolyte layer may be disposed between each of the electrode laminates, and the opposing electrode laminates may be bonded together.
[0049] 5.Other processes The method for producing an all-solid-state battery according to the present disclosure may include a sealing step of attaching a positive electrode terminal and a negative electrode terminal to the battery stack and then sealing the battery stack with an exterior body. The method for producing an all-solid-state battery according to the present disclosure may also include a confining pressure applying step of applying a confining pressure in a thickness direction to the battery stack using a confining jig.
[0050] 6.All-solid-state battery The all-solid-state battery in the present disclosure is typically an all-solid-state lithium-ion secondary battery. The use of the all-solid-state battery is not particularly limited, but examples thereof include power sources for vehicles such as hybrid electric vehicles (HEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. In particular, it is preferable to use the all-solid-state battery as a driving power source for hybrid electric vehicles or electric vehicles. In addition, the all-solid-state battery in the present disclosure may be used as a power source for moving objects other than vehicles (for example, railways, ships, and aircraft), and may be used as a power source for electrical products such as information processing devices.
[0051] The present disclosure is not limited to the above-described embodiment. The above-described embodiment is merely an example, and any configuration that is substantially the same as the technical idea described in the claims of the present disclosure and that exhibits similar effects is included in the technical scope of the present disclosure.
[0052] [Reference example 1] (Preparation of sulfide solid electrolyte) Li2S, P2S5 and LiI were prepared as starting materials. Next, Li2S and P2S5 were weighed to have a molar ratio of 75Li2S·25P2S5 (Li3PS4, ortho composition). Next, LiI was weighed so that the ratio of LiI was 15 mol%. The weighed starting materials were mixed in an agate mortar for 5 minutes, and the mixture was placed in a planetary ball mill container, dehydrated heptane was added, and ZrO2 balls (φ=5 mm) were added, and the container was completely sealed. This container was attached to a planetary ball mill (Fritsch P7) and mechanical milling was performed for 40 hours at a table rotation speed of 500 rpm. After that, heptane was removed by drying at 100 °C, and a sulfide glass was obtained. The obtained sulfide glass was placed in a glass tube and heat-treated at 190 °C for 10 hours to obtain a sulfide solid electrolyte, which is a glass ceramic.
[0053] (Preparation of solid electrolyte layer) The following materials were prepared and mixed: The sulfide solid electrolyte (solid electrolyte) Heptane solution containing 5% by weight of polyvinylidene fluoride binder (binder solution) ·Heptane (dispersion medium)
[0054] The mixture was stirred for 30 seconds with an ultrasonic dispersing device. It was then shaken for 30 minutes to obtain a slurry for the solid electrolyte layer. The obtained negative electrode slurry was applied to an Al foil by a blade method using an applicator. After natural drying, it was dried on a hot plate at 100°C for 30 minutes. As a result, a solid electrolyte layer (thickness 5 μm) was formed on the Al foil.
[0055] [Reference example 2] Polyethylene oxide (PEO; Mw is about 4,000,000) and lithium bistrifluoromethanesulfonylimide (Li-TFSI) were weighed out to a molar ratio of EO unit:Li=20:1. These were dissolved in acetonitrile, and benzoyl peroxide (BPO, radical polymerization initiator) was mixed to a mixture of PEO and Li-TFSI at 10% by weight, and stirred until a homogeneous solution was obtained. The prepared solution was applied onto a PET film by the blade method using an applicator. After natural drying, it was dried on a hot plate at 100°C. As a result, a solid electrolyte layer (thickness 50 μm) was obtained.
[0056] [Reference example 3] The solid electrolyte layer produced in Reference Example 1 and the solid electrolyte layer produced in Reference Example 2 were bonded together to produce a laminated solid electrolyte layer.
[0057] [evaluation] The solid electrolyte layers produced in Reference Examples 1 to 3 were subjected to impedance measurement at 60° C. to determine the DC resistance value. The results are shown in Table 1.
[0058] [Table 1]
[0059] As shown in Table 1, the resistance value of Reference Example 3 was not significantly increased and was generally consistent with the total resistance value of Reference Examples 1 and 2. In this way, it was confirmed that, for example, when an inorganic solid electrolyte is used for the positive electrode layer and the negative electrode layer and a crosslinked polymer electrolyte is used for the solid electrolyte layer, ion exchange of Li ions is possible and the application to all-solid-state batteries is possible. [Explanation of symbols]
[0060] 1 ... Positive electrode layer 2 ... Negative electrode layer 3...Solid electrolyte layer 4...Positive electrode current collector 5...Negative electrode current collector 10...All-solid-state battery
Claims
[Claim 1] a positive electrode structure preparation step of preparing a positive electrode structure having a positive electrode current collector and positive electrode layers disposed on both sides of the positive electrode current collector; a negative electrode structure preparing step of preparing a negative electrode structure having a negative electrode current collector and a negative electrode layer disposed on both sides of the negative electrode current collector; an electrode laminate forming step of bonding the positive electrode structure and the negative electrode structure together by disposing a first solid electrolyte layer containing a first polymer electrolyte between the positive electrode structure and the negative electrode structure to form an electrode laminate; a battery stack formation step of bonding the pair of electrode stacks together to form a battery stack by disposing a second solid electrolyte layer containing a second polymer electrolyte between the positive electrode layer of one of the electrode stacks and the negative electrode layer of the other electrode stack; having the first polymer electrolyte and the second polymer electrolyte are each a cross-linked polymer electrolyte in which a polymer component is cross-linked; The polymer component has a polyether structure in the main chain of the repeating unit, the positive electrode layer and the negative electrode layer each contain an inorganic solid electrolyte.
Citation Information
Patent Citations
superposition electrochemical cell
JP2003523060A
Solid electrolyte battery
JP2006185654A
Binder for electrochemical elements, including multi-layered electrochemical cells.
JP2008546135A
Manufacturing method for all solid battery and all solid battery
JP2015125872A
All-solid lithium secondary battery and secondary battery system including the same
JP2018185883A